A novel E-mode GaN p-MOSFET featuring charge storage layer with high current density. (3rd November 2022) - Chen, Kuangli; Su, Yuanzhang; Ruan, Jiajia; Cai, Yonglian; Zhu, Liyang; Zhang, Bo; Zhou, Qi
Abstract: In this work, a trench gate enhancement-mode GaN p-type metal oxide semiconductor field effect transistor featuring charge storage (CS) layer is proposed, which exhibits an effectively improved current density. Based on device simulations, the current density can be increased by 154% (@ V DS = −5 V, V GS = −7 V) compared with conventional devices without CS layer. Besides, the impact of the critical parameters including AlGaN barrier thickness t, Al mole-fraction x, trench gate depth T recess, and negative charge concentration N CSL on device performance are studied and optimized. In this case, the p-MOSFETs show an on-current | I ON, max | of 14 mA mm −1, V TH of −0.47 V, I ON /I OFF of >10 8, and on-resistance R ON of 0.27 kΩ mm. The proposed GaN p-MOSFETs exhibit a promising method to improve the current drive capability of GaN p-channel devices.